FRI0504 Prognostic Factors of Adult Onset Still's Disease: Analysis of 100 Cases in 3 Tertiary Referral Centers. (15th July 2016) - Ruscitti, P.; Cipriani, P.; Ciccia, F.; Masedu, F.; Iacono, D.; Liakouli, V.; Guggino, G.; Carubbi, F.; Berardicurti, O.; Di Benedetto, P.; Valenti, M.; Triolo, G.; et al.
Abstract : Background: Adult onset Still's disease (AOSD) is rare inflammatory disease [1]. Three different patterns of AOSD have been identified: i. monocyclic pattern, characterized by a systemic single episode; ii. polycyclic pattern, associated with multiple flares, separated by remissions; iii. chronic pattern, related to a persistently active disease with associated polyarthritis [2]. Until now, the treatment of AOSD remains largely empirical, lacking controlled clinical trials [1]. Objectives: We aimed to investigate clinical data of AOSD patients and any possible correlation among these features and the outcome of patients. Methods: Clinical data of 100 AOSD patients were recorded. All patients fulfilled the Yamaguchi AOSD diagnostic [3]. Gender, age, clinical features, disease activity Pouchot's score [4], complications, serum ferritin, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), treatments, comorbidities, patterns and AOSD-associated death, were reported. Furthermore, we evaluated any possible correlation among these clinical features and the outcome of patients, by using linear regression analysis. Results: One hundred consecutive AOSD patients (66 men, 34 women), whose age at diagnosis was 45.35±16.23 (mean±SD), were enrolled. All patients experienced fever, 86 patients showed joints involvement, 79 patients showed splenomegaly, skin rash was present in 78 patients, 62 patients showed hepatic involvement, 57 patients showed enlargement of lymph nodes. The Pouchot's score, 6.11±2.02 (mean±SD), confirmed the activity of the disease. Sixteen patients experienced different complications, mainly the macrophage activation syndrome. A strong increase of inflammatory markers (mean±SD) was observed: serum ferritin was 2560.07±3726.64 ng/mL, ESR was 67.28±26.65 mm/hr, CRP was 78.35±72.76. All the patients received steroids at different dosages, and 55 patients were treated with steroids and immunosuppressive drugs, mainly methotrexate and ciclosporin. Thirty-two patients were treated with biologic agents: 5 with anakinra, 8 with tocilizumab, and 19 with TNF inhibitors. Twenty-nine patients showed the monocyclic pattern, 22 patients showed the polycyclic pattern, 33 patients showed the chronic pattern. AOSD-associated death occurred in 16 patients. Regression analysis showed that Pouchot's score (p=0.011), the presence of any complication (p<0.0001) and associated comorbidities (p<0.0001) correlated with the unfavorable outcome. Conclusions: This study provides information on the clinical, laboratory, therapeutic, and prognostic features in a large cohort of AOSD patients. The Pouchot's score, the presence of complications and comorbidities were significantly associated with the AOSD-associated death. References: Gerfaud-Valentin M, et al. Adult-onset Still's disease, Autoimmun Rev 2014;13, 708–722. Cush JJ, et al. Adult-onset Still's disease. Clinical course and outcome. Arthritis Rheum 1987;30:186–9425. Yamaguchi M, et al. Preliminary criteria for classification of adult Still's disease. J Rheumatol 1992;19:424–30. Pouchot J, et al. Adult Still's disease: manifestations, disease course, and outcome in 62 patients. Medicine (Baltimore) 1991;70:118–36. Disclosure of Interest: None declared